Adenosquamous Carcinoma of the Pancreas Comprise a Heterogeneous Group of Tumors With the Worst Outcome: A Clinicopathological Analysis of 25 Cases Identified in 562 Pancreatic Carcinomas Resected With Curative Intent. Issue 5 (May 2020) - Boecker, Joerg; Feyerabend, Bernd; Tiemann, Katharina; Buchwalow, Igor; Wagner, Kim C.; Oldhafer, Karl J.; Andruszkow, Julia; Daniels, Thies; Boessow, Dorthe; Boecker, Werner; Neumann, Ulf Peter
Abstract : Objectives: Information of the clinicopathological characteristics and outcome data of patients with adenosquamous carcinoma of the pancreas (ASCAP) remains limited. This study's aim is to describe the clinical, pathological, and molecular characteristics of 25 resected ASCAPs. Methods: Of all 25 cases, patient characteristics, follow-up data, and pathological/immunohistological features were reviewed and analyzed. Results: In this 3-institutional retrospective analysis of 562 pancreatic cancer patients, we identified 25 cases with histologically confirmed ASCAP (4.4%). Follow-up was available in 21 ASCAP and 50 pancreatic ductal adenocarcinoma control patients with a median overall survival of 8.2 and 21 months, respectively. Age, tumor size, localization in the tail, lymph node status, and resection margin seem to be the most significant factors of survival in our ASCAP cohort. In contrast to pancreatic ductal adenocarcinoma, positive expression of p63, keratins K5/14, and the epidermal growth factor receptor are a robust marker profile of these tumors. Conclusions: Adenosquamous carcinoma of the pancreas comprises a group of neoplasms in which stage and adverse morphological features contribute to its bad prognosis. Further work must be pursued to improve detection and treatment options to reduce mortality. Specifically, differences in biology might become a target for the development of possible therapies.